Risk-Taking and Optimal Taxation with Nontradable Human Capital - Hu, Zuliu (IMF Working Papers; Working Paper ;, 1992)
What are the effects of taxation on individual/entrepreneurs' risk-taking behavior? This paper re-examines this old question in a continuous time life-cycle model. We demonstrate that the stream of uncertain income from human capital has systematic effects on demand for the risky physical capital asset. If labor supply is inelastic and real wages are known with certainty, then a labor income tax will reduce holdings of the risky physical asset. However, if there are random fluctuations in labor income, then the effect depends on the nature of interaction between wage risk and investment income risk. A labor income tax may actually raise demand for the risky capital asset if human capital risk and physical capital risk are positively correlated. The idiosyncratic risk and nontradability of human capital also have implications for optimal taxation. When the insurance and disincentive effects are jointly taken into account, a Pareto efficient tax structure implies a strictly positive tax rate.